Explanation:
remember the law of cosine :
c² = a² + b² - 2ab×cosC
a, b, c are the 3 sides of the triangle.
C is the opposite angle of side c.
so, this applies to all 3 sides :
a² = b² + c² - 2bc×cosA
b² = a² + c² - 2ac×cosB
a)
cos (x) : its opposite side is 3.
3² = 7² + 5² - 2×7×5×cos(x)
9 = 49 + 25 - 70×cos(x)
9 = 74 - 70×cos(x)
-65 = -70×cos(x)
cos(x) = -65/-70 = 13/14
b)
cos (z) : its opposite side is 7.
7² = 3² + 5² - 2×3×5×cos(z)
49 = 9 + 25 - 30×cos(z)
49 = 34 - 30×cos(z)
15 = -30×cos(z)
cos(z) = 15/-30 = -1/2